The role of teachers in instilling Islamic morals in early childhood through daily school activities - Ali Masran (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
Moral education is a fundamental component in the character formation of young children, especially in Islamic-based education. Instilling Islamic moral values in Early Childhood Education (PAUD) institutions is crucial to building a solid foundation of character. This study aims to explore the role of teachers in instilling Islamic moral values through daily activities at PAUD in Padangsidimpuan. A qualitative approach with a case study method was used, involving observation, interviews, and document analysis. The findings indicate that teachers play an important role through modeling, habituation, and storytelling. Activities such as collective prayers, greeting each other, and helping others are regularly conducted to instill values such as patience, honesty, and compassion. Challenges faced include time constraints, limited teaching materials, and the need for active involvement from parents. This study recommends continuous teacher training, provision of adequate facilities, and strengthening cooperation between schools and parents to support Islamic character education.